The Effect of an 8-Week Aerobic Dance Program on Executive Function in Children. Issue 1 (February 2022) - Zinelabidine, Khawla; Elghoul, Yousri; Jouira, Ghada; Sahli, Sonia
In the current study, we examined the effect of an aerobic dance program as part of physical education (PE) classes on aspects of primary school children's executive functions (EFs) (inhibition, working memory, and cognitive flexibility). Participants were 41 children (21 boys and 20 girls; M age =10.30, SD = 0.50 years, M height = 134.09, SD= 3.9 cm; M weight = 35.61, SD = 7.85 kg) who were divided into an experimental group (EG) and a no-PE control group (CG). The EG followed an aerobic dance intervention as part of their PE program (45 minute sessions two days per week over eight weeks). Participants in both groups performed EF tests before and after the intervention period to evaluate their mental flexibility, inhibition, and working memory. A two-way mixed model repeated measures ANOVA revealed a significant effect of the aerobic dance program on participants' cognitive flexibility (i.e., on Trails Making TestsB-A times and committed errors) ( p <0.001), and on Stroop measures of inhibition (corrected number of words and corrected errors) ( p <0.001 and p <0.01, respectively), with post-hoc analyses showing an improved performance by the EG in working memory (digit recall score) from pre-test to post-test and in comparsion to the CG ( p < 0.001). Thus, this 8-week aerobic dance program promoted EF development among primary school children.